On separating plumes from boundary layers in turbulent convection. (25th June 2022) - Shevkar, Prafulla P.; Vishnu, R.; Mohanan, Sanal K.; Koothur, Vipin; Mathur, Manikandan; Puthenveettil, Baburaj A.
Abstract: Abstract : We present a simple, novel kinematic criterion – that uses only the horizontal velocity fields and is free of arbitrary thresholds – to separate line plumes from local boundary layers in a plane close to the hot plate in turbulent convection. We first show that the horizontal divergence of the horizontal velocity field ( $\boldsymbol {\nabla _H} \boldsymbol {· } \boldsymbol {u}$ ) has negative and positive values in two-dimensional (2D), laminar similarity solutions of plumes and boundary layers, respectively. Following this observation, based on the understanding that fluid elements predominantly undergo horizontal shear in the boundary layers and vertical shear in the plumes, we propose that the dominant eigenvalue ( $λ _D$ ) of the 2D strain rate tensor is negative inside the plumes and positive inside the boundary layers. Using velocity fields from our experiments, we then show that plumes can indeed be extracted as regions of negative $λ _D$, which are identical to the regions with negative $\boldsymbol {\nabla _H} \boldsymbol {· } \boldsymbol {u}$ . Exploring the connection of these plume structures to Lagrangian coherent structures (LCS) in the instantaneous limit, we show that the centrelines of such plume regions are captured by attracting LCS that do not have dominant repelling LCS in their vicinity. Classifying the flow near the hot plate based on the distribution of eigenvalues of the 2D strain rate tensor, we then show that the effect of shear due to the large-scale flow is felt more in regions close to where the local boundary layers turn into plumes. The lengths and areas of the plume regions, detected by the $\boldsymbol {\nabla _H}\boldsymbol {· }\boldsymbol {u}$ criterion applied to our experimental and computational velocity fields, are then shown to agree with our theoretical estimates from scaling arguments. Using velocity fields from numerical simulations, we then show that the $\boldsymbol {\nabla _H}\boldsymbol {· }\boldsymbol {u}$ criterion detects all the upwellings, while the available criteria based on temperature and flux thresholds miss some of these upwellings. The plumes detected by the $\boldsymbol {\nabla _H}\boldsymbol {· }\boldsymbol {u}$ criterion are also shown to be thicker at Prandtl numbers ( $Pr$ ) greater than one, expectedly so, due to the thicker velocity boundary layers of the plumes at $Pr>1$ .